2015
DOI: 10.1111/desc.12355
|View full text |Cite
|
Sign up to set email alerts
|

Difficult temperament and negative parenting in early childhood: a genetically informed cross‐lagged analysis

Abstract: A genetically informed longitudinal cross-lagged model was applied to twin data to explore etiological links between difficult temperament and negative parenting in early childhood. The sample comprised 313 monozygotic (MZ) and dizygotic (DZ) twin pairs. Difficult temperament and negative parenting were assessed at ages 2 and 3 using parent ratings. Both constructs were interrelated within and across age (rs .34–.47) and showed substantial stability (rs .65–.68). Difficult temperament and negative parenting we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 61 publications
5
35
0
1
Order By: Relevance
“…Youth high on reactive temperament had higher anger (10 items, α = .74, factor loading = .83), sadness (10 items, α = .63, factor loading = .77), and behavioral activity (10 items, α = .57, factor loading = .67), as well as lower inhibition (10 items, α = .82, factor loading = −.40) and soothability (10 items, α = .67, factor loading = −.53). Previous studies using similar composite scores of reactive temperament from the TBAQ have demonstrated excellent reliability (Micalizzi, Wang, & Saudino, ), convergent validity with other temperament measures (e.g., Infant Behavior Questionnaire; Majdandžić, Möller, de Vente, Bögels, & van den Boom, ), and good temporal stability from infancy to early childhood (Majdandžić et al., ).…”
Section: Methodsmentioning
confidence: 93%
“…Youth high on reactive temperament had higher anger (10 items, α = .74, factor loading = .83), sadness (10 items, α = .63, factor loading = .77), and behavioral activity (10 items, α = .57, factor loading = .67), as well as lower inhibition (10 items, α = .82, factor loading = −.40) and soothability (10 items, α = .67, factor loading = −.53). Previous studies using similar composite scores of reactive temperament from the TBAQ have demonstrated excellent reliability (Micalizzi, Wang, & Saudino, ), convergent validity with other temperament measures (e.g., Infant Behavior Questionnaire; Majdandžić, Möller, de Vente, Bögels, & van den Boom, ), and good temporal stability from infancy to early childhood (Majdandžić et al., ).…”
Section: Methodsmentioning
confidence: 93%
“…, Kim Chung 0-3 . (Micalizzi et al, 2017) (Perry, Dollar, Calkins, & Bell, 2017) . , • (Lee, Zhou, Eisenberg, & Wang, 2013) .…”
Section: Transactional Relationshipsmentioning
confidence: 99%
“…, (Eisenberg, Cumberland, & Spinrad 1998) J. Kim & Chung, 2015;Micalizzi et al, 2017;Perry et al, 2017) . Abidin (1992) .…”
Section: 영유아의 부정적 정서성mentioning
confidence: 99%
“…For example, a child who is less attentive in infancy may elicit negative reactions from caregivers, creating a negative feedback loop that further impairs the child's development (Wiebe et al, 2014). It should be noted, however, that parent and child behavior is reciprocal, with each member of the dyad shaping the interaction (e.g., Micalizzi, Wang, & Saudino, 2015). Therefore, it is essential to consider the contributions of both dyadic partners to shaping the bidirectional interactions that may promote or hinder child development.…”
Section: State Of the Literaturementioning
confidence: 99%